1999
DOI: 10.1038/sj.jhh.1000782
|View full text |Cite
|
Sign up to set email alerts
|

Out-patient versus in-hospital ambulatory 24-h blood pressure monitoring in heart transplant recipients

Abstract: Objective: To study the effect of the environment-inhospital vs out-patient situation-on blood pressure as measured by ambulatory blood pressure monitoring (ABPM). Patients and methods: Twenty-four hour ABPM was performed sequentially in-hospital and again 9 ± 3 days later on an out-patient basis, in 30 consecutive heart transplant recipients (27 men, median age 56 years, median time post-transplant 3 years). The same equipment was used on both occasions, without any interim change in medical treatment. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Similar to our results, the “white coat effect” of ABPM was described for heart transplant patients. [ 5 ] Conflicting results of another previous study might be related to the older mean age of our study population (84 vs 58 years). [ 6 ] Profound differences of hemodynamics have been reported in older subjects, related to the dramatic increase in prevalence of hypertension with age, from ∼60% in patients in their 60s and 70s to as high as 90% in octogenarians.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Similar to our results, the “white coat effect” of ABPM was described for heart transplant patients. [ 5 ] Conflicting results of another previous study might be related to the older mean age of our study population (84 vs 58 years). [ 6 ] Profound differences of hemodynamics have been reported in older subjects, related to the dramatic increase in prevalence of hypertension with age, from ∼60% in patients in their 60s and 70s to as high as 90% in octogenarians.…”
Section: Discussionmentioning
confidence: 65%
“…A sample size of 40 patients was calculated to have 80% power to detect an effect size of 0.46, using a paired t test with a 0.05 2-sided significance level. [ 5 , 13 ] Assuming a dropout rate of ∼10%, it was planned to enroll 45 patients. All variables were expressed as mean ± SD, or as median accompanied by interquartile range (IQR), if the Shapiro–Wilk test indicated a nonnormal distribution of data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 There has been relatively less investigation regarding whether 24-h ABP values obtained in-hospital differ from those obtained in the usual daily environment. 9,[13][14][15][16] Among five relevant published studies, two showed 24-h ABP to be higher in the outpatient setting, two showed hospital measurements to be higher and one found no effect of hospitalization on 24-h ABP. 9,[13][14][15][16] More specifically, an early study that used continuous intra-arterial BP monitoring in nine patients during controlled periods of activity and rest in both inpatient and outpatient settings showed that mean SBP was higher at home (by 14 mm Hg) than in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an analysis of 30 stable heart transplant recipients showed the 24-h ABP to be lower when assessed at home compared with the first day of hospitalization for an annual checkup. 15 However, these patients do not represent typical hypertensive subjects because they were treated with immunosuppressants (such as cyclosporine, which is known to increase BP 15 ) and were subjected to various non-invasive examinations during the inpatient BP measurement.…”
Section: Discussionmentioning
confidence: 99%